1989
DOI: 10.1002/nau.1930080203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term partial bladder outlet obstruction on the rabbit detrusor: An ultrastructural study

Abstract: It has been shown previously that partial bladder outlet obstruction in the rabbit results in changes in detrusor contractility and biochemical profile [Malkowicz et al., 1986]. The present study was conducted in the same animal model to define the nature and evolution of concomitant structural neuromuscular changes in the detrusor, as the basis for its altered function following partial outlet obstruction. Twenty‐five New Zealand White rabbits, including three normal controls, were used. The bladder was excis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Mature smooth muscle cells will undergo hypertrophy within the muscle bundles in a fashion similar [Elbadawi et al, 1989;Gosling et al, 2000] to that in the rat bladder. Adding to this, a large number of subserosal ®broblasts become transformed [Buoro et al, 1993;Chiavegato et al, 1993;Levin et al, 1995] to myo®broblasts (containing vimentin, smooth muscle actin, and non-muscle myosin) and ®nally to fetal-type smooth muscle cells (containing vimentin, desmin, smooth muscle actin, and smooth muscle myosin).…”
Section: Discussionmentioning
confidence: 94%
“…Mature smooth muscle cells will undergo hypertrophy within the muscle bundles in a fashion similar [Elbadawi et al, 1989;Gosling et al, 2000] to that in the rat bladder. Adding to this, a large number of subserosal ®broblasts become transformed [Buoro et al, 1993;Chiavegato et al, 1993;Levin et al, 1995] to myo®broblasts (containing vimentin, smooth muscle actin, and non-muscle myosin) and ®nally to fetal-type smooth muscle cells (containing vimentin, desmin, smooth muscle actin, and smooth muscle myosin).…”
Section: Discussionmentioning
confidence: 94%
“…It has not been observed in samples of either normal or dysfunctional human detrusor processed for electron microscopic study by identical procedures [52][53][54][55]. Furthermore, it lacked the known ultrastructural features of degenerating, regen erating, and hypertrophic smooth muscle cells [55,57,58], and was associated in all the cases with changes in other tissue elements that clearly were due to edema.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary bladder hypertrophy can be obtained by placing a ligature around the urethra to reduce the lumen (Brent and Stephens 1975;Mattiasson and Uvelius 1982;Levin et al 1984;Steers and De Groat 1988;Elbadawi et al 1989). These experiments are unlike human prostatism in that the partial obstruction is established abruptly 1 There is little or no change in intestinal muscle cell sizes in parenteral nutrition (Nygaard 1967;Nemeth et al 1983).…”
Section: Experimental Models In Laboratory Animalsmentioning
confidence: 99%
“…Degeneration may be more common in human material with impairments of longer duration, often accompanied by inflammation. In the short-term obstructed bladder of rabbits, Elbadawi et al (1989) observed that over 50% of the cell profiles were disintegrating muscle cells.…”
Section: Degeneration Of Muscle Cellsmentioning
confidence: 99%